The Hypsometric Integral Based on Digital Elevation Model for the Area West of Lvliang Mountains in Loess Plateau, Shanxi, China - Duan, Yuying; Pei, Xiangjun; Zhang, Xiaochao (Frontiers in Earth Science, 2022)
A hypsometric integral (HI) is a topographical index with important geomorphological meaning. Based on this index, the integral curve method was used to analyze the HI characteristics of watersheds in major eroded areas on the Loess Plateau of Shanxi Province, China, in combination with 30-m resolution Shuttle Radar Topography Mission data. The study adopted the concept of using geographic objects to subdivide the watershed into a watershed, watershed boundary, shoulder line and main gully, in order to describe the complex topography within the Loess Plateau. Each element was combined with the HI of the watershed as a whole to analyze the erosion development of the watershed in depth. The results showed that HI had a certain scale dependence on the stable area of watershed, but had not a strong dependence on the spatial resolution of digital elevation model data. The HI values for each terrain feature were ranked as: watershed boundary > peak > ridge line > positive terrain > watershed > shoulder line > negative terrain > main gully. Based on the correlation of HI for each terrain feature, the watershed, watershed boundary, and main gully were selected for the HI combination analysis. These results show that the watersheds in the study area are basically mature. In the study area, the HI value of the watershed in the southern loess residual tableland was the largest and the degree of erosion was the weakest, mainly in the area of Jixian and Xiangning. The HI value of the watershed in the north-central part of the loess hilly-gully region was relatively small and the degree of erosion was stronger, especially around Linxian and Xingxian. The study shows that the subdivision of the watershed into topographic feature elements has enriched the study of the HI of the Loess Plateau watershed by carefully delineating the geomorphological characteristic of the watershed.